A Novel Approach to Ransomware: Designing a Safe Zone System - Baykara, Muhammet; Sekin, Baran (Ieee, 2018)
It is vital to protect the files and data for institutions, organizations and individuals. For this, people and institutions develop methods to provide both physical and digital security, and they spend thousands of dollars over the years for measures. Ransomw are is undoubtedly one of the most frequently encountered malicious software that harms people and organizations. These viruses are used to encrypt all important data on the infected computer. Ransomw are usually targets file types such as PDF, Word, Excel that can store important documents, bills, financial data, and makes these documents inaccessible by encrypting them. The restoration of these encrypted files is only possible with the keyword in the hand of the person who wrote the virus. This key word is given by an aggressive fee, which means ransom against documents. These fees are usually very high and there is no guarantee that the attacker will not want more fee. In this paper, it is aimed to find solutions to these problems and to minimize possible harm. In order to do so, an area called safezone has been created and prevented from being replaced by other software by moving important documents to this zone.
6th International Symposium on Digital Forensic and Security (ISDFS) -- MAR 22-25, 2018 -- Antalya, TURKEY
Keywords: information security; ransomware; secure storage; cloud security; computer security